Screening of antimicrobial compound from the sea slug Armina babai (Bangladesh Journal of Pharmacology, 2014)
Different solvents such as acetone, butanol, ethanol, hexane and methanol of Sea slug Armina babai was evaluated for its biomedical properties. Most potent extracts were purified using silica gel column and the active fractions were characterized by TLC, SDS-PAGE and FTIR. Maximum zone of inhibition was recorded against Pseudomonas sp., and minimum zone of inhibition was recorded against Proteus mirabilis by butanol extracts. TLC profiling with Rf value 0.82 indicating the presence of amino acids and peptides. Total protein was estimated as 21.36% with molecular weight range between 13 and 72 kDa in SDS-PAGE. The FT-IR spectrum of fractions, obtained from sea slug, reveals characteristic functional groups range between 465.75 and 3423.82 cm-1. Thus the obtained results indicate the presence of potent antimicrobial compounds in sea slug A. babai may pave the way to explore the potential development of new compounds to be launched in the pharmaceutical filling.